Two Years of Gynecomastia Caused by Leydig Cell Tumor. (19th July 2018) - Zeuschner, Philip; Veith, Christian; Linxweiler, Johannes; Stöckle, Michael; Heinzelbecker, Julia
Abstract : Gynecomastia is a common incidental finding in males that can be caused by various benign or malignant diseases. In rare cases, it results from Leydig cell tumors, a rare entity accounting for 3% of all testicular neoplasms. Some of them are hormonally active but seldom cause symptomatic endocrine disturbance. Here we report on a 32-year-old male presenting with gynecomastia which he had already been suffering from for two years. Although he had been seen by three other specialists, including a urologist, none of them found the small mass in the upper pole of his right testis. We decided to perform testis-sparing surgery which confirmed the diagnosis of a hormonally active Leydig cell tumor. During follow-up, hormonal status normalized, and gynecomastia began to resolve.